The change of sex ratio in Lamprey based on predator and Logistic model - Zhang, Ronghang (Transactions on Computer Science and Intelligent Systems Research, 2024)
This paper studies the sex ratio and resource availability of lamprey population, through the predator model and Logistic model of lamprey population dynamic simulation. Differential equations were used to dynamically describe the dynamic changes within lampreys population, and then the effects of changes in sex ratio on the food chain, population reproduction rate, habitat occupation and resource availability were analyzed. Optimize and analyze the population dynamic change model to simulate the impact of changing sex ratio on the population. Based on the competition and mutualism between lampreys and parasites, combined with the food chain in which they are located, the ecological model of multi-species interaction is re-established on the basis of the original model to solve the problem, and the sensitivity analysis of the final result is carried out.We found that changes in the sex ratio of lampreys populations can provide an advantage to other species.